MUTU PELAYANAN GIZI DENGAN TINGKAT KEPUASAN PASIEN - Iin Rachmawati; Wiwik Afridah (Jurnal Ilmiah Kesehatan, 2014)
The quality of nutritional service is one of the indicators of the quality hospital service. Therefore, the purpose of this research was to find out the relationship between the quality of hospital nutritional service and the level of patient’s satisfaction hospitalized in Teratai Room of Islamic Hospital located on Jemursari, Surabaya.The design of research was analytic cross sectional. The population of patient’s hospitalized ≥ 3 days in Teratai Room of Islamic Hospital located on Jemursari, Surabaya by 40 respondents, a sample of 36 respondents, taken using a consecutive sampling.The independent variable was the quality of hospital nutritional service, where as the dependent one was the level of patient’s satisfaction. Instrument using a questionnaire sheet. Analysis of the data by the Fisher Exact Test. The result of research showed that most of the respondent (52,2%) said the quality of nutritional hospital service is good and nearly half (47,2%) said they were satisfied. Fisher’s Exact Test statistic test value obtained ρ = 0.007 describing that there was a significant relationship between the quality of hospital nutritional service and the level of patient’s satisfaction hospitalized in the hospital. The research has concluded that most of the quality nutritional of hospital service is have good and patient’s have satisfaction. The nutritional official must be through, when process and prepare a dish up a food a patient